2019
DOI: 10.1002/lsm.23048
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 311‐nm Titanium:Sapphire laser and 308‐nm excimer laser treatment for vitiligo: A randomized controlled non‐inferiority trial

Abstract: Objectives: The 308-nm excimer laser (EL) has been widely used for localized vitiligo. The recently developed Titanium:Sapphire laser, emits a wavelength of 311 nm, would be expected to be as effective as excimer laser in treatment of vitiligo but few controlled trials have been reported. We sought to compare the efficacy and safety of the TSL and EL as vitiligo treatments. Methods: A randomized controlled non-inferiority trial based on split-body was conducted. Patients with stable vitiligo between June 2016 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Vitiligo is a prevalent depigmentation disease characterized by melanocyte death, not only by the loss of melanin, resulting in milky white patches appearing on the skin . It is the most prevalent depigmented disease that affects 1%‐4% of the world's population …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitiligo is a prevalent depigmentation disease characterized by melanocyte death, not only by the loss of melanin, resulting in milky white patches appearing on the skin . It is the most prevalent depigmented disease that affects 1%‐4% of the world's population …”
Section: Introductionmentioning
confidence: 99%
“…1 It is the most prevalent depigmented disease that affects 1%-4% of the world's population. 2 Recent proof has shown that vitiligo is attributed to the disruption of melanogenesis and metabolic function. 3 The abnormal loss of melanin outcomes in vitiligo-related pathological procedures.…”
Section: Introductionmentioning
confidence: 99%
“…10 A recently developed 311-nm titanium sapphire laser was shown not to be inferior to EL treatment in a randomized noninferiority study with 74 paired lesions in 21 patients. 14 Another meta-analysis 13 assessed the benefit of adding topical therapy to EL and showed superior repigmentation for combination therapy with calcineurin inhibitors, [15][16][17][18] however, insufficient evidence was found for combination therapy with topical vitamin D3 [19][20][21] analogues and corticosteroids. 22 Furthermore, the efficacy of EL with topical tacrolimus was assessed in the metaanalysis of Chang.…”
Section: Excimer Lasermentioning
confidence: 99%
“…Laser modalities that have been used in vitiligo include excimer laser/lamp (308 nm), Titanium:Sapphire Laser (311 nm), (Bae et al., 2019) fractional Carbon dioxide laser (10,600 nm), (Ezzedine, et al., 2018) and helium‐neon laser. (Lan et al., 2009) Excimer laser emits a monochromatic light of wavelength 308 nm, and it usually does not lead to perilesional hyperpigmentation due to its small spot size, however, this limits its use to localized disease.…”
Section: Managementmentioning
confidence: 99%
“…(Lopes et al., 2016) A randomized controlled trial found that therapeutic efficacy and safety of Titanium:Sapphire laser was comparable to excimer laser in localized vitiligo. (Bae et al., 2019) Better marginal repigmentation has been noted with the combination of CO 2 laser and NB‐UVB as compared to NB‐UVB alone. (Ezzedine, et al., 2018).…”
Section: Managementmentioning
confidence: 99%